Impact of Social Media on Adolescent Mental Health and Ethical Development: A Qualitative Study on Early Character Formation in Sarolangun Regency - Hidayat, Nur; Abroto, Abroto; Dzunur'aini, Rosyidah (AL-ISHLAH: Jurnal Pendidikan, 2024)
Adolescent psychiatry reveals that 95.4% of adolescents aged 16-24 exhibit anxiety symptoms, and 88% show signs of depression, largely due to excessive social media use, resulting in character decline and apathy. This study explores the role of early character building in improving the formation of ethics in children in Sarolangun Regency, addressing concerns related to the negative effects of social media. A qualitative, descriptive approach was employed to investigate how habituation practices contribute to the development of student ethics. The study focused on five schools in Sarolangun Regency: SDIT AL Fatih, SDIT Rahmatul Ummah, SDIT AL Kahfi, SDN 1, and SDIT AS-Salam. Data collection involved interviews and observations of students, teachers, and parents to assess their roles in ethical development. The findings demonstrate that while technological advancements offer various benefits, they also introduce significant challenges, particularly in the realm of student behavior. Teachers actively work to mitigate the negative impacts of social media by providing guidance, instruction, and education on its dangers. Additionally, parents play an essential role in fostering ethical behavior, contributing significantly to children's moral development through consistent support and proper guidance. Both educators and parents are pivotal in guiding students' ethical growth amidst the increasing influence of social media. The combined efforts of these stakeholders ensure that children develop strong ethical foundations, helping counteract the potential negative impacts of technology. The study highlights the importance of early ethical education and the need for collaboration between teachers and parents to effectively guide children in the responsible use of social media.